2020
DOI: 10.1039/d0tc00634c
|View full text |Cite
|
Sign up to set email alerts
|

Two different mechanisms of stabilization of regular π-stacks of radicals in switchable dithiazolyl-based materials

Abstract: Regular π-stacks of dithiazolyl radicals can be rendered stable via two different mechanisms depending on the relative disposition of neighboring radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 86 publications
3
15
0
Order By: Relevance
“…The control of reversible changes in a particular physical channel such as electrical, magnetic, or optical response is important in the process of information transmission and shows promising applications in sensors, displays and switching devices. [76][77][78][79][80] A simultaneous involvement of two or more different physical channels can open new avenues in electronics. Awaga et al found that 1,3,5-trithia-2,4,6-triazapentalenyl (TTTA) could undergo first order magnetic phase transistion with a wide thermal hysteresis loop at temperature range from 230 to 305 K. The balance of exchange and electrostatic energies at high temperature (HT) and low temperature (LT) influenced ll the intermolecular stacking and radical interaction, which resulted the change of magnetic property from paramagnetic to diamagnetic together with the change of crystal color from purple to green (Figure 10A).…”
Section: Applications Multiple Channel Bistabilitymentioning
confidence: 99%
“…The control of reversible changes in a particular physical channel such as electrical, magnetic, or optical response is important in the process of information transmission and shows promising applications in sensors, displays and switching devices. [76][77][78][79][80] A simultaneous involvement of two or more different physical channels can open new avenues in electronics. Awaga et al found that 1,3,5-trithia-2,4,6-triazapentalenyl (TTTA) could undergo first order magnetic phase transistion with a wide thermal hysteresis loop at temperature range from 230 to 305 K. The balance of exchange and electrostatic energies at high temperature (HT) and low temperature (LT) influenced ll the intermolecular stacking and radical interaction, which resulted the change of magnetic property from paramagnetic to diamagnetic together with the change of crystal color from purple to green (Figure 10A).…”
Section: Applications Multiple Channel Bistabilitymentioning
confidence: 99%
“…When cooled, the alternate layers of radicals are shifted laterally to produce arrays of dimers. Detailed computational studies involving ab initio molecular dynamics simulations point out that the regular stacking motif of the HT polymorphs does not correspond to a minimum in the potential energy surface of the system but is a result of fast intrastack pair-exchange dynamics. The radicals continually exchange with the adjacent radical with which they form an eclipsed π-dimer in the HT phase. This unique electron dynamics is a major source of the vibrational entropy stabilizing the HT phase of the radicals and plays a prime role in determining the LT → HT transition.…”
Section: Electron Dynamics Affecting Magnetic Bistabilitymentioning
confidence: 99%
“…Minimum energy path connecting two degenerate dimerized π-stacks of PDTA (1-LT); the maximum of the path is associated with the regular arrangement of the radicals (1-HT). Reproduced from ref with permission from The Royal Society of Chemistry.…”
Section: Electron Dynamics Affecting Magnetic Bistabilitymentioning
confidence: 99%
“…These typically transition from one state to another by a first-order phase transition, which involves two potential energy minima. However, if the energy barrier is low, a dynamic equilibrium with rapid switching between two states can exist, known as pair-exchange dynamics (PED). ,, In fact, two degenerate minimum-energy structures involve radical dimers, but the averaged structure appears like a stack of equidistant radicals. Spin-Peierls transition by PED is a second-order phase transformation. , It is clear that a PED-type phase transition is possible only if structural differences are small.…”
Section: Introductionmentioning
confidence: 99%